2020
DOI: 10.1002/smll.202002621
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Noble Metal Nanoclusters Loaded Protein Hydrogel Exhibiting Anti‐Biofouling and Self‐Healing Properties for Electrochemiluminescence Biosensing Applications

Abstract: analytical method over the past few decades, and holds great promise in various analytical application fields, especially in the analysis of biological samples. [1-3] By far, remarkable efforts have been made to develop various types of ECL based biosensing systems, [4,5] and the recent introduction of new ECL materials or mechanisms, such as metal-organic frameworks, aggregation-induced emission luminogens or single atom catalysts, further improved the performance and application ranges of ECL based biosensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…In addition to detecting GSH, the sensing system also has anti-biofouling and self-healing properties. These characteristics make it suitable for long-term biosensing applications [97]. Wang et al reported a hydrogel biosensor that can be used to detect calmodulin (CaM).…”
Section: Biosensorsmentioning
confidence: 99%
“…In addition to detecting GSH, the sensing system also has anti-biofouling and self-healing properties. These characteristics make it suitable for long-term biosensing applications [97]. Wang et al reported a hydrogel biosensor that can be used to detect calmodulin (CaM).…”
Section: Biosensorsmentioning
confidence: 99%
“…As one light-emission phenomenon initiated by the electrochemical reactions, electrochemiluminescence (ECL) integrated the superiorities of electrochemistry and chemiluminescence, [1][2][3] which endowed it with the advantages of high sensitivity, well controllability, wide linear range, rapid response, 2017, Carrara et al found that the supramolecular assembled Pt complexes exhibited higher ECL efficiency than that of their monomers with negligible ECL emission, which was analogous to AIE and defined as "aggregation-induced electrochemiluminescence" (AI-ECL). [33] This phenomenon demonstrated that the enhanced ECL emission resulted from the effective restriction of intramolecular motions (RIM).…”
Section: Introductionmentioning
confidence: 99%
“…They have already been widely used in chemical biosensing, biomedical tracing, target analyte detection and other elds owing to their simple operation, stable optical properties, and low toxicity. [33][34][35] Bovine serum albumin-stabilized gold nanoclusters (BSA-AuNCs) are considered one of the excellent uorescent nanomaterials as they have shown satisfactory accuracy and specicity in the detection of various ionic and small-molecule drugs. [36][37][38] The interaction between AAI and BSA has been reported in a preliminary study, demonstrating the quenching effect of BSA.…”
Section: Introductionmentioning
confidence: 99%